Gambaran Plasenta Dan Berat Bayi Lahir Pada Ibu Hamil Yang Terinfeksi Malaria Di Puskesmas Sentani Kabupaten Jayapuratahun 2024 - Hermayani, Hermayani; Trisnawati, Endang; Syahrani, Fadhilah Aulya (Barongko: Jurnal Ilmu Kesehatan, 2025)
Malaria is usually spread by the bite of a female Anopheles mosquito that has the disease., which feeds on blood to support egg development. Anopheles mosquitoes are typically active at night. During the blood-feeding process, the mosquito’s saliva containing Plasmodium parasites in the gametocyte stage enters the human body. Within the body, the male and female sexual forms (gametes) of the parasite unite to form a cyst-like sporozoite. These sporozoites then travel to the liver, where they multiply and develop into exoerythrocytic schizonts. Malaria can have negative impacts on pregnant women and their unborn babies. These effects may include maternal and infant death or a range of complications affecting the mother, fetus, and newborn. This research seeks to explore how malaria during pregnancy affects the weight of the placenta and the weight of newborns. A quantitative method with a descriptive approach was used. The study subjects were pregnant women infected with malaria who gave birth at the Sentani Health Center. Among the 12 respondents infected with malaria, all had placental weights of less than 500 grams. Meanwhile, the 20 respondents who were not infected with malaria all had placental weights of 500 grams or more. The Chi-square test for placental weight yielded a p-value of 0.000, indicating a significant effect of malaria infection in pregnant women on placental weight at Sentani Health Center, Jayapura Regency, in 2024.